Kontruksi Identitas Diri Remaja Penggunaan Media Sosial Instagram: Studi Fenomenologi di Universitas Islam Negeri Sumatera Utara (UINSU) - Shakira Putri Anjeli; Khoirul Jamil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research explores the role of Instagram in strengthening the religious identity of teenagers, especially UINSU students Class of 2020. Using a qualitative phenomenological approach, this research involved 7 informants from the Islamic Counseling and Communication Sciences department. The findings show that Instagram is an important platform for teenagers to reflect and strengthen religious identity, especially through sharing religious content such as preaching quotes. An inclusive campus environment influences the formation of this identity. Motivations for sharing religious content include providing knowledge, providing motivation, and conveying da'wah. However, using Instagram can also create identity conflicts between religion and the desire for free expression. The implications of this study provide a new understanding of the formation of teenagers' religious identity through social media, as well as highlighting the complexity of maintaining identity in the digital world and everyday life.